Rywalizacja państw w kosmosie - Stankiewicz, Wojciech (Przegląd Politologiczny, 2018)
The paper emphasizes that outer space has become an object of interest for different states relatively recently. Therefore, there is no detailed international law to regulate the activity of states in outer space. Current regulations were mainly drawn up at the turn of the 1960s, and they do not fully correspond to the reality of today. The drawing up of modern space law will be a dynamic process owing to the rapid evolution of space technology and an increasing exploration potential. As the activity of states in outer space is rapidly changing, laws to be drawn up may frequently be prepared ad hoc, in response to the newly emerging problems. It may be exceptionally difficult to enact a new convention to regulate general issues of outer space, in the way it has been done with respect to the law of the sea, as some countries (in particular the United States) may oppose the limitation of their plans to explore and utilize outer space. In order to maintain peace and balance, it may be necessary to establish a new international organization for the purpose of dealing with outer space. This organization would provide a forum to solve disputes, such as those concerning the development of satellite systems, the principles of teledetection, or armaments in space. A considerable portion of inter-state disputes concerning outer space will have to be solved by bilateral agreements, reached through a compromise, as there are no specialized organs authorized to act in the realm of outer space. A dynamically conducted exploration of outer space depends on the amount of expenditure allocated to the space programs of individual states. The amount of financing available is influenced by the economy (at the time of the slowdown that began in 2008 space agencies have had to envisage limited budgets). The prestige of space exploration is an aspect of particular importance. In order to increase its importance in the international arena, states are ready to allocate considerable means for spectacular space activities. It can be observed at present that states are increasingly competing with each other for prestige rather than for strategic purposes. This can easily be observed with respect to the developing countries, such as China and India. The pace of activities in space will be influenced by the ability of the states to cooperate. The specific nature of great space investments usually requires huge expenditure, therefore it would be advantageous to combine the financial contributions of various states. Joint projects would promote peaceful utilization of outer space.